Role of doppler in fetal growth restriction - Patel, Chirag K.; Shah, Parul T.; Patel, Rina V.; Deliwala, Kruti J.; Patel, Rohan; Pandya, Viral (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Fetal growth restriction is an important and particularly challenging problem for modern obstetricians and paediatricians. The present study is to correlate the importance of Doppler velocimetry and perinatal outcome in cases of growth restricted foetuses by comparing perinatal outcome of control & study groups with normal and abnormal Doppler waveforms. Methods: A study and a control group comprising of 50 pregnant women having growth restricted foetuses in each group was matched for all other confounding factors except for Doppler changes. These patients were followed up and the perinatal outcomes of FGR foetuses having Doppler changes was compared with those having normal Doppler studies. Results: In our study, alteration in both MCA and UmbA Doppler was associated with perinatal morbidity and NICU admissions in 64% and mortality in 28%. Doppler changes showing altered CPR less than 1 had adverse outcome with NICU admission in 61% and mortality in 34%. Alteration in DV Doppler was associated with perinatal morbidity and NICU admissions in 17% cases and mortality in 83% cases, with no pregnancies having a healthy outcome. Among high-risk pregnancies with suspected IUGR, the use of Doppler assessment significantly decreases the likelihood of labor induction, caesarean delivery, and perinatal deaths. Conclusions: Abnormal Doppler waveform changes indicate adverse perinatal outcome of pregnancies with FGR. Doppler study helps to reduce perinatal mortality and morbidity by timely and appropriate interventions.